Catalysing Social Change through a Community-Based Religious Educational Model in Rural Indonesia - Salman Yafi (PT Agung Media Publisher, 2026)
Rural communities in Indonesia frequently face limited access to high-quality Islamic education due to geographical distance and financial constraints. This community service programme addresses these barriers by optimising local resources at Rumah Tahfidz Zhillaalul Qur’an in Solok Regency to enhance Qur’anic and Arabic literacy through an Asset-Based Community Development (ABCD) approach. The methodology commenced with asset mapping, identifying 3 highly qualified local educators. Data was triangulated through participatory observations of 45 active students, in-depth interviews with 15 local stakeholders, and online surveys completed by 120 prospective nationwide learners, alongside continuous social media analytics across 4 digital platforms. The implementation integrated offline and online learning models across four developmental stages. The optimisation of local expertise successfully strengthened existing programmes, significantly improving the recitation quality (makhārij al-ḥurūf and tartīl) of the 45 students. Digital innovation effectively expanded institutional outreach, directly facilitating the evidence-based development of three new hybrid initiatives: online adult tahfidz-tahsin, offline Arabic language instruction for local youth, and nationwide online Arabic courses. The findings demonstrate that synergising the ABCD approach with hybrid learning models provides a sustainable and replicable framework for rural Islamic education. The programme not only enhanced religious literacy but also fostered a paradigm shift, proving that high-quality religious education can be locally based, affordable, and highly effective in transforming communities from dependent recipients to empowered agents.